Anionic Polyelectrolyte Hydrogel as an Adjuvant for Vaccine Development - Mariya Kozak; Nataliya Mitina; Alexandr Zaichenko; Vasyl Vlizlo (MDPI AG, 2020)
Vaccination is one of the main methods for the specific prevention of infectious diseases. The disadvantage of vaccination is the use of pathogens (live or attenuated viruses and bacteria) that can lead to the development of a disease. Recombinant technologies are capable of producing specific DNA or protein molecules that possess antigenic properties and do not cause disease. However, individual antigen molecules are low-immunogenic, and therefore, require conjugation with a compound possessing stronger immunogenic properties. In this study, we examined the immunogenic properties of the new anionic copolymer consisting of glycidyl methacrylate, butyl acrylate, triethylene glycol dimethacrylate, and acrylic acid, in mice. The experimental polymer induced a stronger immunogenic response than aluminum hydroxide. The histological studies have established that immunization both with aluminum hydroxide and the polymer studied does not cause damage to the liver, kidneys, or the spleen. No negative side effects were observed. It has been concluded that the new synthetic anionic polyelectrolyte hydrogel (PHG) has a potential as an adjuvant for vaccine development.